Rational choices of communities in purchasing housing on the urban fringe of Yogyakarta - Emilia Putri Purnama; Nanda Harda Pratama Meiji (Penerbit Universiti Kebangsaan Malaysia, 2025)
Yogyakarta has experienced a notable increase in population density due to an influx of migrants from various regions. This demographic growth has led to a surge in land prices across the city. As a result, many young families who do not yet own a house have become increasingly concerned and have chosen to purchase housing on the outskirts. This study aims to examine in greater depth the rational choices made by communities when deciding to purchase housing in peripheral areasi. This research employed a qualitative research design. The subjects in this study are young families who decided to purchase housing in urban fringe areas. The findings indicate that the primary rationale behind this decision is the need to adjust their budgetary allocations, given that residential properties in the urban fringe areas are considerably more affordable than those in the city center. Additional motivations include a preference for a tranquil atmosphere in the countryside, the availability of adequate facilities (although not yet fully comprehensive), and convenient accessibility, despite the considerable distance from the city center of Yogyakarta.